2013
DOI: 10.1103/physrevd.87.044028
|View full text |Cite
|
Sign up to set email alerts
|

Destroying extremal Kerr-Newman black holes with test particles

Abstract: It has been shown that a nearly extremal black hole can be overcharged or overspun by a test particle if radiative and self-force effects are neglected, indicating that the cosmic censorship might fail. In contrast, the existing evidence in literature suggests that an extremal black hole cannot be overcharged or overspun in a similar process. In this paper, we show explicitly that even an exactly extremal black hole can be destroyed by a test particle, leading to a possible violation of the cosmic censorship. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 24 publications
6
79
1
Order By: Relevance
“…Instead, it turns out that cosmic censorship is still preserved, for most of the geometries considered, with few very special exceptions. Together with previous results on Kerr [5] or charged BHs [31,32], higher-dimensional BHs [6] and BHs in non-asymptotically flat spacetimes [10,30,33,34], our results indicate that destroying event horizons is a difficult task. We remain as ignorant as before on the precise reasons for this.…”
Section: Exceptions: Jp and Cpr Metricssupporting
confidence: 86%
“…Instead, it turns out that cosmic censorship is still preserved, for most of the geometries considered, with few very special exceptions. Together with previous results on Kerr [5] or charged BHs [31,32], higher-dimensional BHs [6] and BHs in non-asymptotically flat spacetimes [10,30,33,34], our results indicate that destroying event horizons is a difficult task. We remain as ignorant as before on the precise reasons for this.…”
Section: Exceptions: Jp and Cpr Metricssupporting
confidence: 86%
“…conducted on the conjecture for not only black holes of Einstein's theory of gravity, but also anti-de Sitter (AdS), lower-dimensional, and higher-dimensional black holes [18][19][20][21][22][23][24][25][26][27][28][29][30]. From a thermodynamic point of view, the conjecture is quite consistently related to the laws of thermodynamics.…”
Section: Jhep11(2017)129mentioning
confidence: 99%
“…Interestingly, the physics of general relativity prohibits such a process, the test particles with sufficient charge and angular momentum, which can overcharge the black hole get repelled and does not enter the event horizon. Similar analysis has been done on various scenarios, and it is always found that the formation of a naked singularity by overcharging is not possible [12][13][14][15][16][17][18][19][20][21]. On the other hand, Hubeny has shown that if the initial configuration is near extremal, it is possible to overcharge a Reissner-Nordstrom (RN) black hole using test particle absorption [22].…”
Section: Introductionmentioning
confidence: 66%